PERANCANGAN ARTWORK DESIGN PRODUK MERCHANDISE MENGGUNAKAN SABLON DIRECT TO GARMENT PADA BOHO STORE - Sinaga, Rommel; Malau, Leo Vinanda (Politeknik Negeri Media Kreatif)
Artwork design in the form of screen printing on merchandise products can be of more value to the merchandise product and give an artistic and exclusive impression to the design compared to other screen printing designs, in the design of screen printing designs using the artwork the authors design the design starting from in the form of manual drawings using equipment such as Drawing Pens, graphite pencils, charcoal pencils, ballpoints, Chinese ink and others, then through the coloring and editing or digital stages using design software such as Photoshop CC so that later it can be printed using a DTG (Direct to Garment) printing machine in form of screen printing on merchandise products.